Syntheses, Characterizations, and Inhibition Activities Against Coxsackievirus B3 of Iodobenzoic Hydrazide Functionalized Hexamolybdates - Wang, Long-Sheng; Guo, Chao; Hu, Da; Zhao, Yan-Xi; Liu, Hui-Hui; Dong, Yu-Jia; Sun, Shang-Bin; Liu, Xing; Hu, Kang-Hong; Wei, Yan-Hong (Frontiers in Chemistry, 2022)
A class of iodobenzoyldiazenido-functionalized POMs (TBA)3 [Mo6O18(=N=NCOAr)] (Ar = Ph-o-I (1); Ph-m-I (2); Ph-p-I (3); Ph-3,4-I2(4); Ph-2,3,5-I3(5) (TBA = tetrabutylammonium) were prepared via the refluxing reaction of α-octamolybdates, DCC, and corresponding hydrazides in dry acetonitrile. Their structures were determined by Fourier-transform infrared spectroscopy, ultraviolet–visible spectra, X-ray photoelectron spectroscopy, hydrogen-1 nuclear magnetic resonance, and high-resolution mass spectrometry. Research on the biological activity of title compounds shows that L3, L5, 3, and 5 demonstrate potent inhibitory activity against coxsackievirus B3 and low in vitro cytotoxic activity against Hep-2 cell lines. The covalent linkage between the iodobenzoyldiazenido components and POMs can enhance the molecular inhibitory efficiency of iodobenzohydrazides.